Valentinian and Sethian Apocalyptic Traditions - Attridge, Harold W. (Journal of early Christian studies, 2000)
The paper reexamines the relationship between "apocalyptic" and "gnostic" traditions, on the assumption that global definitions of these phenomena are problematic. Valentinian and Sethian corpora in the Nag Hammadi collection display different appropriations of apocalyptic literary forms and conceptual schemes. Apart from a few late works with traces of Valentinian positions, this tradition largely ignores features characteristic of apocalyptic literature. Valentinian eschatology seems to be founded primarily on philosophical cosmology and psychology. Sethian texts preserve many features of Jewish revelatory literature, and many details associated with various eschatological schemes familiar from apocalyptic sources. The most extensive use of the characteristic "heavenly ascent" topos in Sethian literature, however, seems to be a third-century development, perhaps responding to contemporary forms of religious propaganda.